2019
DOI: 10.1111/inr.12496
|View full text |Cite
|
Sign up to set email alerts
|

Non‐nursing tasks as experienced by nurses: a descriptive qualitative study

Abstract: Background Different concepts have been used to date (e.g. non‐nursing tasks, organizational work) to define tasks performed by clinical nurses other than nursing care. However, the true essence of nursing work is still poorly understood mostly because nurses are lacking an appropriate lexicon to describe their practice. Aims To describe non‐nursing tasks as experienced by nurses, exploring antecedents and consequences as perceived in daily practice. Methods A descriptive qualitative study from 2015 to 2016. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 31 publications
5
49
1
Order By: Relevance
“…Nurses are challenged in fulfilling their duties in complex and demanding work environments (Combrinck 2018) which they described as painful and unbearable in a study conducted by Storaker et al (2017) in a university hospital in Norway. Exposure to excessive administration and ever‐increasing expectations towards nurses’ professional roles (Grosso et al 2019) leaves nurses vulnerable in their professional dignity. The discrepancy between desired and realized nursing practice prevents them from living their humanistic nursing values.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses are challenged in fulfilling their duties in complex and demanding work environments (Combrinck 2018) which they described as painful and unbearable in a study conducted by Storaker et al (2017) in a university hospital in Norway. Exposure to excessive administration and ever‐increasing expectations towards nurses’ professional roles (Grosso et al 2019) leaves nurses vulnerable in their professional dignity. The discrepancy between desired and realized nursing practice prevents them from living their humanistic nursing values.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses, as a professional cadre, are generalists who can be deployed in many settings and are more economically affordable compared with several other and often more expensive professionals employed in the health sector (Grosso et al 2019 ). Tasks are therefore expected to continue to shift to RNs in the foreseeable future to meet the health needs of populations; hence, the evolvement of the scope of practice appears inevitable.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the overlapping roles of health workers (within nursing and across disciplines) appear prevalent. Grosso et al ( 2019 ) concluded that nurses, in their daily practice, occupy various non-nursing roles below, above and horizontal to their competencies. They found (Grosso et al 2019 ) that RNs function both in and outside other healthcare professional spaces and that the nurse’s role appears to be a contingent one.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations